Compensation, Performance and Effect on Turnover Intention Home Delivery Personnel - Endang Sundari; Sri Harini; Erni Yuningsih (Indonesian Journal of Social Research (IJSR), 2019)
Human Resources (HR) is the important asset especially for an organization performance. Considering about the biggest benefit of HR company, it will be better if a company give attention to all HR aspects. One of the aspect is compensation. The aim in giving compensation is to increase working performance and to minimize employee's resignation or tunover intention. The purpose of this research is to know the compensation effect to the performance and tunover intention in Maternity Hospital. Analysis simple regression is used as a method on the research, and 54 employees are used as the population. Partially the result of this research shows that compensation is affected positif and sgnificant to work performance. Compensation affected negatif and significant to tunover intention.